2011
DOI: 10.1111/j.1476-4431.2011.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute aldicarb toxicity in dogs: 15 cases (2001–2009)

Abstract: Acute aldicarb toxicosis carries a good prognosis for survival and hospital discharge with treatment. Supportive care should be considered for at least 18-24 hours to monitor for response to therapy and development of respiratory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
(134 reference statements)
0
18
0
8
Order By: Relevance
“…Muscarinic ACh receptors are found on the surface of smooth muscles, heart and exocrine glands, and nicotinic ACh receptors are found in the central nervous system and on the surface membrane of skeletal muscles. Hence, the clinical manifestation of carbamate poisoning, as vomiting, diarrhoea, urination, bronchorrea, bradycardia, miosis are result of muscarinic overstimulation, and tachycardia, hypertension, respiratory depression, muscle fasciculation, muscle weakness and paralysis, are result of nicotinic overstimulation (Anastasio and Sharp, 2011;Baron and Merriam, 1988;Gupta, 1994;Risher et al, 1987). Similar to prior studies (Flanagan et al, 2005;Forrester and Stanley, 2004;Khan, 2012;Leibson and Lifshitz, 2008;Xavier et al, 2007b), some of these clinical manifestations were reported by owners and clinicians in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Muscarinic ACh receptors are found on the surface of smooth muscles, heart and exocrine glands, and nicotinic ACh receptors are found in the central nervous system and on the surface membrane of skeletal muscles. Hence, the clinical manifestation of carbamate poisoning, as vomiting, diarrhoea, urination, bronchorrea, bradycardia, miosis are result of muscarinic overstimulation, and tachycardia, hypertension, respiratory depression, muscle fasciculation, muscle weakness and paralysis, are result of nicotinic overstimulation (Anastasio and Sharp, 2011;Baron and Merriam, 1988;Gupta, 1994;Risher et al, 1987). Similar to prior studies (Flanagan et al, 2005;Forrester and Stanley, 2004;Khan, 2012;Leibson and Lifshitz, 2008;Xavier et al, 2007b), some of these clinical manifestations were reported by owners and clinicians in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The number of cases seen depends on criminal activity within the area 64 . The use of aldicarb to poison animals is, however, not only restricted to South Africa, with reports indicating large-scale intentional malicious poisoning of dogs and other species from the United Sates of America 2,20 and Spain 43 . The extensive use of aldicarb in agriculture, and resultant easy accessibility, has been suggested as 1 of the reasons why the malicious use of aldicarb in recent years has increased, in preference to the more traditional poisons such as strychnine 43,57,59,62 .…”
Section: Background Information To the Problem In South Africamentioning
confidence: 99%
“…To date, there have been very few published articles discussing the treatment of aldicarb poisoning in dogs 2,64 , with most published reports focusing on human cases 9,31,66 . Aldicarb poisoning is an emergency 2,51,64 and patients may die within minutes after ingestion due to respiratory failure 22,31,51 . Therefore, veterinarians need to be able to promptly diagnose aldicarb toxicity and start with effective treatment immediately to offer a reasonable prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Other known drugs and toxins that have the potential to cause hyperlactatemia include: nucleoside HIV reverse transcriptase inhibitors, 240 the biguanide anti-hyperglycemic agents (phenformin, metformin), 16,145,146,[292][293][294][295] linezolid, 240,[296][297][298] isoniazid, 240,299,300 5-fluorouracil, 301,302 the sugar alcohols fructose, sorbitol, and xylitol, 29,268,[303][304][305] as well as acetylcholinesterase inhibitor and carbamate pesticides. [306][307][308][309][310]…”
Section: Miscellaneousmentioning
confidence: 99%